THE IMPACT OF PERCEIVED VALUE AND PRODUCT INNOVATION TOWARD LOYALTY’S BRAND ON VIDEO PREMIUM APPLICATION SERVICES - Didi Tarmidi; Kevin Putra Wijaya (SEAN Institute, 2023)
Expanding deals is certainly the objective of each commerce within the world, but showcase conditions are challenges that must be passed such as advertise patterns, competition, mechanical advancements, and other factors. Video could be a video-on-demand application that has seen a advertise share concurring to justwatch.com of 1 percent in 1 year whereas other competitors developed by 2-4%, of course, Video must keep up existing shoppers to stay faithful whereas trying to find ways to grow the showcase. This research wants to investigate the impact of Client Seen Esteem and Item Development on Brand Dependability. The strategy used may be a quantitative strategy with 100 respondents utilizing the Video application with different relapse investigation calculations handled within the SPSS25 computer program. This result appears analysts that video application clients in Bandung that Client Seen Esteem and Item Development at the same time and in part have a critical impact on Brand Loyalty.